Tunnelling of the 3rd kind: a test of the effective non-locality of quantum field theory - Gardiner, Simon A.; Gies, Holger; Jaeckel, Joerg; Wallace, Chris J. (epl, 2013)
Integrating out virtual quantum fluctuations in an originally local quantum field theory results in an effective theory which is non-local. In this letter we argue that tunnelling of the 3rd kind —where particles traverse a barrier by splitting into a pair of virtual particles which recombine only after a finite distance— provides a direct test of this non-locality. We sketch a quantum-optical setup to test this effect, and investigate observable effects in a simple toy model.
Gesehen am 26.02.2021